2021
DOI: 10.3390/ijms222413623
|View full text |Cite
|
Sign up to set email alerts
|

Spatially Resolved Expression of Transposable Elements in Disease and Somatic Tissue with SpatialTE

Abstract: Spatial transcriptomics (ST) is transforming the way we can study gene expression and its regulation through position-specific resolution within tissues. However, as in bulk RNA-Seq, transposable elements (TEs) are not being studied due to their highly repetitive nature. In recent years, TEs have been recognized as important regulators of gene expression, and thus, TE expression analysis in a spatially resolved manner could further help to understand their role in gene regulation within tissues. We present Spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
(41 reference statements)
0
6
0
Order By: Relevance
“…In contrast, DNA transposons encode proteins that allow excision from the genome locus and its insertion elsewhere. Most TEs are unable to transpose as a result of the accumulation of inactivating mutations, and, based on their divergence rate, they can also be classified into "young" or "old" TEs [13,14]. In addition to inactivating mutations, host genomes have several mechanisms to regulate TE expression at the transcriptional and post-transcriptional level, such as DNA methylation, chromatin modifications, RNA interference pathways and through activity of Krüppel-associated box (KRAB) zinc-finger proteins, amongst others (reviewed in [15,16]).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, DNA transposons encode proteins that allow excision from the genome locus and its insertion elsewhere. Most TEs are unable to transpose as a result of the accumulation of inactivating mutations, and, based on their divergence rate, they can also be classified into "young" or "old" TEs [13,14]. In addition to inactivating mutations, host genomes have several mechanisms to regulate TE expression at the transcriptional and post-transcriptional level, such as DNA methylation, chromatin modifications, RNA interference pathways and through activity of Krüppel-associated box (KRAB) zinc-finger proteins, amongst others (reviewed in [15,16]).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, LINEs and LTRs were expressed also at the P30 and Adult stages. Although TE expression was thought to only occur at early developmental stages as consequences of global epigenetic derepression, and in disease and stress conditions, as consequence of cellular malfunction, we and others have shown that they indeed become transcriptionally active in both mouse and human healthy, adult tissues (20,24). Such reports suggest that TEs could have functional implications in normal and proper cell functioning.…”
Section: Te Expression Across the Scrna-seq Atlas Of The Murine Smg D...mentioning
confidence: 69%
“…These reads are subsequently classified into one of the following categories based on the number of mapping locations: locus-specific, if the MAPQ is equal to 255 (indicating unique alignment), or subfamilyspecific, if the MAPQ was less than 255 (indicating multiple alignment). We have previously taken advantage of the usage of this metric in Spatial Transcriptomics data, which follows a similar computational process during alignment and demultiplexing, to that of scRNA-Seq (20). Although not all TE locus are retrieved, it still shows an improvement to the default strategy of directly summarizing expression at the subfamily level (12).…”
Section: Methodsmentioning
confidence: 99%
“…83 Valdebenito-Maturana et al carried out a spatial expression analysis of transposable elements (TEs), developed SpatialTE tools, and applied them to the spinal cord data of ALS-infected mice. 95 Interestingly, the expression of TEs in the dorsal and ventral horns was higher than that observed in the medial or distal regions of the spinal cord. Some LTR and non-LTR TE (such as LINE and SINE) were activated in the disease.…”
Section: Application Of Spatial Transcriptomics (St) In Scimentioning
confidence: 90%
“…Further validation of clinical samples found that sphingomyelin signal can be used as a therapeutic target for ALS 83 . Valdebenito‐Maturana et al carried out a spatial expression analysis of transposable elements (TEs), developed SpatialTE tools, and applied them to the spinal cord data of ALS‐infected mice 95 . Interestingly, the expression of TEs in the dorsal and ventral horns was higher than that observed in the medial or distal regions of the spinal cord.…”
Section: Application Of Spatial Transcriptomics (St) In Scimentioning
confidence: 99%